The Rural Gothic in American Popular Culture - Murphy, B. author. aut Link
VII, 257 p.
Keywords: The Rural Gothic in American Popular Culture argues that complex and often negative initial responses of early European settlers continue to influence American horror and gothic narratives to this day. The book undertakes a detailed analysis of key literary and filmic texts situated within consideration of specific contexts.